Pengaruh Metode Latihan Servis Bawah Bola Voli Dengan Tingkat Kecepatan Servis - Su, Welly; Sugiono; Sukowati, Anton (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The aim of this research was to determine the effect of the volleyball bottom serve training method on the level of service determination of class IX students at SMP Negeri 24 Malaumkarta. This research is descriptive research, the total sample is 25 students. The results of the research show that the highest service level for male and female students in Class IX of SMP Negeri 24 Malaumkarta is in the